Nintedanib in an elderly non-small-cell lung cancer patient with severe steroid-refractory checkpoint inhibitor-related pneumonitis: A case report and literature review - Pan, Lei; Meng, Fanqi; Wang, Wei; Wang, Xu-hao; Shen, Hui; Bao, Pengchen; Kang, Jian; Kong, Delei (Frontiers in Immunology, 2023)
Immune checkpoint inhibitors tremendously improve cancer prognosis; however, severe-grade immune-related adverse events may cause premature death. Current recommendations for checkpoint inhibitor-related pneumonitis (CIP) treatment are mainly about immunosuppressive therapy, and anti-fibrotic agents are also needed, especially for patients with poor response to corticosteroids and a longer pneumonitis course. This is because fibrotic changes play an important role in the pathological evolution of CIP. Here, we report a case demonstrating that nintedanib is a promising candidate drug for CIP management or prevention, as it has potent anti-fibrotic efficacy and a safety profile. Moreover, nintedanib could partially inhibit tumor growth in patients with non-small-cell lung cancer, and its efficacy can be improved in combination with other anti-tumor therapies.